The Influence of CEO's Education Level and Accounting Professional Background on Financial Slack - Syahbinah Syahbinah; Novrys Suhardianto (Jurnal Dinamika Akuntansi, 2025)
Purposes: This study examines the influence of the CEO's education level and accounting background on financial slack, providing insights into how executive characteristics shape economic decisions. Methods: The research uses data from non-financial public companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022, covering 1,001 firm-year observations. The study employs multiple linear regression analysis to assess the relationship between CEO characteristics and financial slack, controlling for firm-specific and macroeconomic factors. Findings: The results show that the CEO's education level does not significantly affect financial slack. On the contrary, this study finds that CEOs with an accounting background can reduce financial slack.    Novelty: This research supports the upper echelons theory, which argues that top executives' characteristics influence strategic decisions. Specifically, CEOs with an accounting background shape financial slack decisions. The findings offer valuable insights for companies on accounting qualifications when hiring CEOs during crises, emphasizing financial slack as crucial for sustaining survival and growth. Additionally, this research aids investors in assessing corporate leadership for better investment decisions, contributing to corporate governance discussions on financial strategies and executive decision-making in uncertain economic conditions.